Properties of simian virus 40 transcriptional intermediates isolated from nuclei of permissive cells. - Shani, M (1977)
A nucleoprotein complex that is an intermediate in viral transcription has been isolated from simian virus 40 (SV40)-infected BSC-1 cells after lysing infected nuclei with Sarkosyl. It contain DNA, DNA-dependent RNA polymerase II, and nascent RNA chains. RNA chain elongation continues for several hours in vitro and is dependent on exogenous ribonucleoside triphosphates. The complex sediments in neutral sucrose gradients with a main peak at about 24 to 26S. When the nascent RNA on the complex is treated with RNase A, a fraction of the RNA remains resistant to RNase and is hydrogen bonded to the DNA template. The pulse-labeled RNase-resistant RNA can be chased into RNase-sensitive RNA, indicating that it is located at the 3' terminus of the RNA chain. The rate of RNA displacement from the DNA template is consistent with an average rate of RNA chain elongation of 15 to 30 nucleotides per min. At least 70% of the RNA synthesized in this in vitro system is SV40 specific. Hybridization with the separated strands of SV40 DNA and with fragments of SV40 DNA generated with endonucleases HindII + III indicates that this RNA is complementary to all regions of the "late" SV40 DNA strand. Studies of SV40 RNA synthesis in this partially purified preparation at early and late times after infection should provide a way of locating promoter sites for transcription and identifying the form of SV40 DNA that serves as a template for late transcription.